2020
DOI: 10.1080/1343943x.2020.1847668
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer responsiveness of high-yielding drought-tolerant rice in rainfed lowlands

Abstract: Recent advances in rice breeding in tropical Asia led to the release of high-yielding drought-tolerant cultivars. Together with the use of these cultivars, improved nutrient management under drought should further increase rice productivity in rainfed lowland ecosystems. The objectives of this study were to evaluate cultivar differences in the responses of plant growth and grain yield to fertilizer application regimes. We compared 13 drought-tolerant rice cultivars with two irrigated rice cultivars under three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…Taking that into consideration, reproductive tiller per unit area is a crucially significant morpho-physiological character of paddies that is considered to be a high N content indicator in cultivated soil [46,47]. Furthermore, the spike-bearing numbers/unit area, filled grains number and spike weights are the main determining components for obtaining high grain quantities [48].…”
Section: Effect Of Azolla Compost Synthetic Fertilizers and Their Com...mentioning
confidence: 99%
“…Taking that into consideration, reproductive tiller per unit area is a crucially significant morpho-physiological character of paddies that is considered to be a high N content indicator in cultivated soil [46,47]. Furthermore, the spike-bearing numbers/unit area, filled grains number and spike weights are the main determining components for obtaining high grain quantities [48].…”
Section: Effect Of Azolla Compost Synthetic Fertilizers and Their Com...mentioning
confidence: 99%
“…This was the case under rainfed conditions in Magoola 2017 and Idete in 2016, where yields were low due to poor grain filling, and the resultant harvest indices were lower than those observed in similar treatments under adequate water supply. The minimal effect of fertiliser application observed in this study due to drought relates with previous studies where limited fertilisation effect and low rice yields have been reported as a result of drought at panicle initiation, flowering or grain filling stage (Banayo et al, 2020;Castillo et al, 2006;Yang et al 2019). Drought during our study occurred from panicle initiation to grain filling stage in Magoola 2017, and at vegetative, panicle initiation and grain-filling stage in Idete 2016 (Supplementary Table S2.3).…”
Section: Discussionsupporting
confidence: 81%
“…The DT check variety, NSIC Rc192, obtained a grain yield of 1.78-6.33 t ha −1 under rainfed conditions and 0.98-4.21 t ha −1 under controlled-drought conditions with an average of 4.32 and 2.18 t ha −1 , respectively. The average grain yield in the rainfed conditions was relatively higher than those observed in other studies, 3.63 t ha −1 in other regions in the Philippines [40,41] and 3.50 t ha −1 in Nepal [42,43]. The grain yields for the DT check variety were reduced by 8-67% and 47-88% under the rainfed and controlled-drought conditions, respectively, relative to the irrigated control.…”
Section: Grain Yieldmentioning
confidence: 57%